Sr distribution as proxy for Ca distribution at depth in SXRF analysis of mm‐sized carbonaceous chondrites: Implications for asteroid sample return missions. (2nd March 2022) - Tkalcec, B. J.; Tack, P.; De Pauw, E.; Vekemans, B.; Nakamura, T.; Garrevoet, J.; Falkenberg, G.; Vincze, L.; Brenker, F. E.
Abstract: Reliable identification of chondrules, calcium‐aluminum‐rich inclusions (CAIs), carbonate grains, and Ca‐phosphate grains at depth within untouched, unprepared chondritic samples by a nondestructive analytical method, such as synchrotron X‐ray fluorescence (SXRF) computed tomography (CT), is an essential first step before intrusive analytical and sample preparation methods are performed. The detection of a local Ca‐enrichment could indicate the presence of such a component, all of which contain Ca as major element and/or Ca‐bearing minerals, allowing it to be precisely located at depth within a sample. However, the depth limitation from which Ca‐K fluorescence can travel through a chondrite sample (e.g., ∼115 µm through material of 1.5 g cm −3 ) to XRF detectors leaves many Ca‐bearing components undetected at deeper depths. In comparison, Sr‐K lines travel much greater distances (∼1700 µm) through the same sample density and are, thus, detected from much greater depths. Here, we demonstrate a clear, positive, and preferential correlation between Ca and Sr and conclude that Sr‐detection can be used as proxy for the presence of Ca (and, thus, Ca‐bearing components) throughout mm‐sized samples of carbonaceous chondritic material. This has valuable implications, especially for sample return missions from carbonaceous C‐type asteroids, such as Ryugu or Bennu. Reliable localization, identification, and targeted analysis by SXRF of Ca‐bearing chondrules, CAIs, and carbonates at depth within untouched, unprepared samples in the initial stages of a multianalysis investigation insures the valuable information they hold of pre‐ and post‐accretion processes in the early solar system is neither corrupted nor destroyed in subsequent processing and analyses.